2021
DOI: 10.1038/s41598-021-92118-x
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of metabolic parameters on 18F-fluorodeoxyglucose positron tomography/computed tomography in classical rectal adenocarcinoma

Abstract: We aimed to investigate the prognostic value of the metabolic parameters of 18F-fluorodeoxyglucose positron emission tomography/computed tomography (FDG PET/CT) in classical rectal adenocarcinoma (CRAC). We retrospectively reviewed 149 patients with CRAC who underwent preoperative 18F-FDG PET/CT at initial diagnosis followed by curative surgical resection. 18F-FDG PET/CT metabolic parameters including maximum standardized uptake value (SUVmax), metabolic tumour volume (MTV), and total lesion glycolysis (TLG) f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 32 publications
1
14
0
1
Order By: Relevance
“…This technique allows doctors to access standardized image texture information and to stand out informed inference. To date, radiomics has been proven to effectively predict biological characteristics of numerous types of cancers (7,19,20). In GC patients, although studies were preliminary, radiomics texture analyses have been proven to not only improve prediction of survival but also provide additional information in oncologic practice related to benign and malignant nodule differentiation, prediction of lymph node metastasis, histological subtype classification, response to chemotherapy assessment, and mutation type identification (9,15,17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This technique allows doctors to access standardized image texture information and to stand out informed inference. To date, radiomics has been proven to effectively predict biological characteristics of numerous types of cancers (7,19,20). In GC patients, although studies were preliminary, radiomics texture analyses have been proven to not only improve prediction of survival but also provide additional information in oncologic practice related to benign and malignant nodule differentiation, prediction of lymph node metastasis, histological subtype classification, response to chemotherapy assessment, and mutation type identification (9,15,17).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that the prognosis and malignant degree of GC were closely related to imaging features. For example, metabolically active tumor volume (MATV) has been proven to be a prognostic factor in patients with GC (7); Li et al constructed a radiomics signature of 18-F fluorodeoxyglucose PET/CT for prediction of GC survival (8); Jiang et al selected 19 potential predictors from the 269 features identified, which provided a neoteric angle for individualized diagnosis and prediction of malignancy potential for GC patients (9); Jiang et al developed machine learning for predicting the pathological stage for GC (8); and studies established a deep learning radiomics model for effectively predicting the lymph node metastasis of local GC (10). However, these radiomics studies did not show satisfied diagnostic efficiency, and many controversial results still existed.…”
Section: Introductionmentioning
confidence: 99%
“…Em relação ao CCR, os marcadores tumorais são importantes para implicar recorrência e metástase pós-operatória, além de serem úteis para indicar realização de PET-CT (Zhang et al, 2019) O exame PET-CT é importante por caracterizar biologicamente as lesões tumorais, avaliar o seu metabolismo, presença de hipóxia e proliferação celular, tornando possível otimizar planos de tratamento (Grut, Revheim, Line & Dueland, 2018). A partir da análise da impregnação da glicose nos tecidos alvos, auxilia no manejo terapêutico e na avaliação do prognóstico, com uso de parâmetros metabólicos, como o valor máximo de captação padronizado (SUVmax), o volume metabólico do tumor e a glicose total da lesão (Choi et al, 2021). Esse exame aumenta, significativamente, a detecção de CCR Research, Society andDevelopment, v. 11, n. 9, e1711931173, 2022 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v11i9.31173 metastático oculto (Ko, Baghdadi, Love & Sparano, 2020), além de ser útil na detecção de metástases em linfonodos de pacientes com CCR e linfonodos edemaciados em TC (Todate et al, 2021).…”
Section: Pet-ctunclassified
“…VAT is closely associated with dysregulated visceral fat activity increasing adipokines related to systemic inflammation, and can play a role in oncogenesis and metastatic lesion. 1,12 The increased inflammatory condition of VAT activity might influence the status of LN in CRC patients. [13][14][15][16][17] Byung Wook Choi et al were among the few to retrospectively show the predictive value of metabolic parameters on 18 F-FDG PET/CT in classical rectal adenocarcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16][17] Byung Wook Choi et al were among the few to retrospectively show the predictive value of metabolic parameters on 18 F-FDG PET/CT in classical rectal adenocarcinoma. 12 Another study by Sung Hoon Kim et al retrospectively showed the prognostic factor of 18 F-FDG PET/CT for LN metastasis in rectal cancer, 18 whereas Kisoo Pahk et al retrospectively showed the predictive value of functional VAT activity measured by preoperative 18 F-FDG PET/CT for regional LN or distant metastasis in CRC patients. 1 Given that the findings of these studies have been inconsistent in showing the exact maximum standardized uptake value (SUV max ) readings indicative of a higher risk of metastases, more data is needed to verify whether PET/CT can assist in early metastases identification in CRC patients.…”
Section: Introductionmentioning
confidence: 99%